Financial Constraints and Tax Avoidance in Mining Companies Listed on the Indonesia Stock Exchange 2020–2022 - Mira; Wahyuni Wahyuni; Nurdiani (Universitas Muhammadiyah Makassar, 2025)
This study investigates the effect of financial constraints on tax avoidance among mining companies listed on the Indonesia Stock Exchange (IDX) during the period 2020–2022. Mining firms operate in a capital-intensive and highly regulated environment, making them vulnerable to fluctuations in commodity prices, financing frictions, and liquidity pressures. These conditions heighten the relevance of examining whether financial constraints influence corporate tax planning behavior. Using a quantitative research design, the study analyzes panel data from 24 mining companies that consistently reported complete audited financial statements over the three-year period, resulting in 72 firm-year observations. Financial constraints are measured using the Hadlock–Pierce (HP) Index, while tax avoidance is proxied by the Cash Effective Tax Rate (CETR), which captures real cash taxes paid relative to pre-tax income. Several control variables—firm size, profitability, leverage, and capital intensity—are included to account for operational and structural characteristics of mining firms. Panel regression analysis is conducted using the Hausman test to determine the appropriate model, supplemented by classical assumption testing to ensure statistical validity. The results are expected to provide empirical evidence on whether financially constrained mining firms engage more aggressively in tax avoidance as a strategy to preserve liquidity during periods of economic uncertainty, including the COVID-19 pandemic. The study contributes to the literature by offering sector-specific insights into the financial determinants of tax avoidance in a highly regulated extractive industry and provides implications for policymakers, investors, and corporate managers regarding financial pressure, compliance behavior, and fiscal governance.